Predicting interethnic bridging social capital in youth ethnic diversity engagement: the role of interethnic interaction and intercultural sensitivity - Tamam, Ezhar; Hashmi, Madiha (Routledge, 2015)
In this study, the authors examined the relationships between interethnic interaction, intercultural sensitivity and interethnic bridging social capital among students of different ethnicities at a Malaysian public university. Results of the regression analysis on data from 447 self-administered questionnaires revealed that while interethnic interaction and intercultural sensitivity are significantly correlated with interethnic bridging social capital at the bivariate level, only intercultural sensitivity has a direct relationship and significantly predicts interethnic bridging social capital. The finding underscores the role of intercultural sensitivity on interethnic bridging social capital development through ethnic diversity engagement.